ANALISIS PENGUKURAN DAN PELAPORAN BIAYA KUALITAS SEBAGAI ALAT PENGENDALIAN BIAYA KUALITAS PADA CV. BLACK CUP INDO UTAMA MANADO - Pabusa, Herman; Alexander, Stanly; Maradesa, Djeini (Universitas Sam Ratulangi, 2020)
Quality costs are costs incurred by the company in order to improve product quality which refers to all costs incurred to prevent the occurrence of defective goods or costs that must be incurred due to defective goods. Quality costs can be divided into two groups, namely the first quality costs associated with control activities consisting of prevention costs and valuation costs and the second is costs associated with failure activities consisting of internal failure costs and external failure costs. This study aims to determine the measurement and reporting of quality costs as a quality cost control tool on the CV. Indo Utama Black Cup Manado. The research method used in this thesis research is a descriptive method in which the purpose of each data collected is analyzed then drawn a conclusion and the type of research used is descriptive qualitative. The results obtained that the measurement and reporting of quality costs on the CV. Indo Utama Manado Black Cup has not yet taken cost measurements and has not presented separate quality cost reporting, so it cannot be used as a quality cost control tool.